Raman and photoluminescence of Er3+-doped SnO2 obtained via the sol-gel technique from solutions with distinct pH - Ravaro, Leandro Piaggi [UNESP]; Tabata, Américo Sheitiro [UNESP]; Oliveira, José Brás Barreto de [UNESP]; Scalvi, Luis Vicente de Andrade [UNESP] (Elsevier B.V., 2010)
Raman and infrared photoluminescence measurements are carried out for Er3+-doped SnO2 pellets (hard-pressed powders) obtained by the sol-gel technique from colloidal suspensions with distinct pH. Raman data indicate that bulk vibration modes are dominating for neutral pH. When the pH is modified, there is an intensity increase of acoustic surface modes. The evaluation of bulk and crystallite surface vibration modes indicates that the contribution of the bulk decreases for pH above the neutral and decreases even further for acid pH, becoming the surface vibration modes as dominating in this case. Infrared photoluminescence data indicate that the intensity of the emission generated from the I-4(13/2) -> I-4(15/2) transition is strongly dependent on the pH of colloidal suspension, which may broaden the emission peaks due to overlapping of Stark levels. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Tin dioxide; Sol-gel; Erbium; pH; Luminescence